LiMn2O4 – MXene nanocomposite cathode for high-performance lithium-ion batteries - Ali, Muntaha Elsadig Siddig (2024)
Lithium-ion batteries still face many significant challenges for practical applications, including low discharge capacity, cyclic efficiency, initial coulombic efficiency, areal performance, volumetric capacity, and high materials cost. LiMn2O4 (LMO) characterized by its spinel structure, is a highly appealing cathode material attributed to its remarkable energy density, cost-effectiveness, and minimal environmental impact. However, LMO experiences capacity fading while shifting between the C rates. The 2D material MXene with its very high electrical conductivity functions as a conductive matrix, allowing for volume expansion and contraction during Li+ intercalation while retaining structural and electrical connections. In this work, the LiMn2O4-MXene (LMO-MX) nanocomposite was synthesized by a cost-effective microwave-assisted chemical coprecipitation and examined. Structural characterization confirmed the effective synthesis of LMO-MX nanocomposite. Electrochemical characterizations demonstrate that LMO-MX nanocomposites exhibit outstanding electrochemical performance, with an initial specific discharge capacity of roughly 111 mAhg-1 at 0.1 C, and capacity retention of 95.2% after 100 cycles in contrast to the pristine LMO which gave an initial specific discharge capacity of 97 mAhg-1 and cyclability of 89.3%. The incorporation of MXenes enhances the electrochemical characteristics of LMO cathode material and implies that MXene-based nanocomposites might be useful as cathodes in high-performance lithium-ion batteries.